Taking it a step farther: acknowledging librarians' systematic review work in the promotion or tenure process. - Raszewski, Rebecca; Goben, Abigail (Journal of the Medical Library Association, 2026)
Librarians' contributions to systematic review projects receive inconsistent recognition within promotion or tenure processes. A review of thirty-six academic libraries' norms and procedures revealed only two that mentioned systematic reviews. Recognition and inclusion of systematic reviews and other evidence synthesis is further complicated by variance in recognition of interdisciplinary work. This commentary provides recommendations for academic library leadership to establish standards for documenting and evaluating systematic review work in annual reviews and promotion or tenure, explicitly recognizing the value of participation in interdisciplinary scholarship, inclusion of search strategies as a scholarly output, and providing guidance for the external review process. We close with a call to action for professional organizations to establish centralized guidelines to ensure the full recognition of librarianship and scholarly participation in systematic reviews.